Effect of ammonia stress on carbon metabolism in tolerant aquatic plant—Myriophyllum aquaticum. (August 2020) - Gao, Jingqing; Liu, Lina; Ma, Na; Yang, Jiao; Dong, Zekun; Zhang, Jingshen; Zhang, Jinliang; Cai, Ming
Abstract: In this study, the tips of Myriophyllum aquaticum ( M. aquaticum ) plants were planted in open-top plastic bins and treated by simulated wastewater with various ammonium-N concentrations for three weeks. The contents of related carbohydrates and key enzyme activities of carbon metabolism were measured, and the mechanisms of carbon metabolism regulation of the ammonia tolerant plant M. aquaticum under different ammonium-N levels were investigated. The decrease in total nonstructural carbohydrates, soluble sugars, sucrose, fructose, reducing sugar and starch content of M. aquaticum were induced after treatment with ammonium-N during the entire stress process. This finding showed that M. aquaticum consumed a lot of carbohydrates to provide energy during the detoxification process of ammonia nitrogen. Moreover, ammonia-N treatment led to the increase in the activitives of invertase (INV) and sucrose synthase (SS), which contributed to breaking down more sucrose to provide substance and energy for plant cells. Meanwhile, the sucrose phosphate synthase (SPS) activity was also enhanced under stress of high concentrations of ammonium-N, especially on day 21. The result indicated that under high-concentration ammonium-N stress, SPS activity can be significantly stimulated by regulating carbon metabolism of M. aquaticum, thereby accumulating sucrose in the plant body. Taken together, M. aquaticum can regulate the transformation of related carbohydrates in vivo by highly efficient expression of INV, SPS and SS, and effectively regulate the osmotic potential, thereby delaying the toxicity of ammonia nitrogen and improving the resistance to stress. It is very important to study carbon metabolism under ammonia stress to understand the ammonia nitrogen tolerance mechanism of M. aquaticum . Graphical abstract: Image 1 Highlights: The decrease in carbohydrates of M. aquaticum was induced by ammonium-N treatment. Enhanced activitives of INV, SS and SPS were observed under ammonium-N stress. Carbohydrates in vivo can be regulated by enhancing INV, SS and SPS activitives.